The Influence of Work Discipline And Work Environment On The Performance of Employess In Resto Sambel Idjo Kediri Branch - Ahmad Ihdal Umam; Enni Sustiyak; Yogi Yunanto (Faculty of Economics, Merdeka University Surabaya, Indonesia, 2024)
Employee performance is one of the most influential factors in the system work, be it an organization or company, and whether a company or organization is good or not can be seen from how good or not the performance of its employees is. To avoid the bad side of employee performance, motivation and a work environment are needed so that all activities carried out by employees will be in accordance with existing procedures in the company and can improve the quality and optimal performance of a company or organization. This research aims to analyze the influence of motivation and work environment on employee performance. The work discipline variable has a positive and significant effect on employee performance at Resto Sambel Idjo Kediri Branch. This means that the better the work discipline, the better the performance given by the employees of Resto Sambel Idjo Kediri Branch. The work environment has a positive and significant effect on employee performance at Resto Sambel Idjo Kediri Branch. This means that the better the work environment provided by the company, the better the performance provided by the employees of Resto Sambel Idjo Kediri Branch. Discipline and work environment simultaneously have a significant influence on employee performance at the Kediri Branch of Sambel Idjo Resto. This means that the variables of work discipline and work environment both have an influence on employee performance